Suppression of the non-linear background in a multimode fibre CARS endoscope - Pikálek, Tomáš; Stibůrek, Miroslav; Simpson, Stephen; Čižmár, Tomáš; Trägårdh, Johanna (Biomedical optics express, 2022)
Multimode fibres show great potential for use as miniature endoscopes for imaging deep in tissue with minimal damage. When used for coherent anti-Stokes Raman scattering (CARS) microscopy with femtosecond excitation sources, a high band-width probe is required to efficiently focus the broadband laser pulses at the sample plane. Although graded-index (GRIN) fibres have a large bandwidth, it is accompanied by a strong background signal from four-wave mixing and other non-linear processes occurring inside the fibre. We demonstrate that using a composite probe consisting of a GRIN fibre with a spliced on step-index fibre reduces the intensity of the non-linear background by more than one order of magnitude without significantly decreasing the focusing performance of the probe. Using this composite probe we acquire CARS images of biologically relevant tissue such as myelinated axons in the brain with good contrast.